PENGARUH PENDIDIKAN PELATIHAN DAN PRESTASI KERJA TERHADAP KOMPENSASI KARYAWAN PT. BANK RAKYAT INDONESIA KANTOR WILAYAH PEKANBARU - Andila, Novel; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to determine the influence of educational training and job performance of the compensation received by employees of Bank Rakyat Indonesia Pekanbaru Regional Office. The method of analysis used in this study is descriptive statistical analysis method and inferential statistics through Multiple Regression. The method of research using survey methods, of the number of population of 1101 employees of Bank Rakyat Indonesia Regional Office Pekanbaru taken a sample of 294 respondents with a stratified random sampling technique. Before testing the hypothesis, test the validity and reliability of the primary data questionnaire using SPSS version 17.0. Regression equations were then tested with analysis of classical assumption of normality test, Multicollinearity Test, Test and Test Heteroskidastity autocorrelation. Analysis of the influence of the independent variables with the dependent variable analysis performed with the t test, F test, the coefficient of determinant (R2) and correlation coefficient (R). The results showed partially and simultaneously, training and educational factors and the job performance have an influence on the compensation received by employees of Bank Rakyat Indonesia Pekanbaru Regional OfficeKeywords: Education Training, Job Performance, Compensation